KOMPETENSI PROFESIONAL GURU TERHADAP MUTU LULUSAN SMK SE-KECAMATAN TENJOLAYA KABUPATEN BOGOR - Musyaropah, Wardatul; Huda, Samsul; Awaludin S., Muhamad Robie (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
This study aims to determine the effect of teacher professional competence on the quality of vocational high school graduates in Tenjolaya District, Bogor. The type of research used is quantitative, with a survey method. Data collection is accumulated using a closed questionnaire, so that respondents can only choose one answer that is appropriate to their circumstances, the questionnaire includes a number of answers that have been determined by the researcher based on various statements, both positive and negative. The measurement of the data uses a Likert scale on five alternative answers, for the questionnaire variable (Y) graduate quality contains 50 items and the variable (X) teacher professional competence contains 44 items that are tested for validity using the Pearson product moment test and tested for reliability using Cronbach's alpha, so that valid and reliable statement items are obtained for the graduate quality variable 45 items and the teacher professional competence variable, namely 33 items, with research subjects as many as 65 respondents taken using probability sampling and simple random sampling techniques, where sampling is carried out randomly so that all subjects are treated and placed equally. The data analysis method applied is inferential statistics using simple regression tests, supported by the SPSS version 26 program, to determine the effect between the teacher's professional competence variable (X) on the quality of graduates (Y). The results of the study indicate that there is an effect between teacher professional competence on the quality of graduates by obtaining a significance value of 0.005 <0.05. So it can be interpreted that the teacher's professional competence variable (X) has a positive effect on the quality of graduates (Y). Therefore, in order to improve the quality of graduates, it is hoped that school institutions can improve the professional competence of teachers in teaching according to their expertise.